NPID DOUBLE HYPERBOLIC CONTROLLER WITH PARTICLE SWARM OPTIMIZATION (PSO) TECHNIQUE FOR XY TABLE BALLSCREW DRIVE SYSTEM - Abdullah, L.; Junoh, S.C.K.; Retas, Z.; Salim, S.N.S.; Nordin, M.H. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
: The difficulty in determining the parameters of NPID Double Hyperbolic controller tends to apply an optimization technique. In this study the optimization technique named as Particle Swarm Optimization (PSO) technique is applied on the NPID Double Hyperbolic controller for XY Table Ballscrew drive system. The inspiration of the PSO is based on the behavior of bird flock in which all particles are placed at random position and supposed to move randomly in a defined direction in the search space. Eventually, each particle moves along the direction of its best previous positions to discover a new better position with respect to some error measures. In addition, the PSO technique is able to obtain the optimum parameters in order to produce a better performance of a system based on an error function obtained from tracking error. The PSO using NPID Double Hyperbolic controller scheme is designed via MATLAB/Simulink software and the PSO is run for 10 times in obtaining a better RMSE result. For future work, it is recommended to explore the superiority features offered in another optimization for better judgment in improving a better convergence of optimization process.